The Language of Interlingual Subtitles: Studying the f Word in Skins - NIKOLIC, KRISTIJAN (International Journal of Language, Translation and Intercultural Communication, 2019)
The language of interlingual subtitles and the effect it has on viewers is a concern for viewers of subtitled audiovisual content, subtitlers, and SVOD1 services such as Netflix2, as well as other cable, national and commercial broadcasters that show subtitled content. Subtitles are a popular form of audiovisual translation and their usage is growing worldwide. Conveying conversational dialogues from one language via subtitles to another may not come without obstacles as subtitles are a reduced, written, form of text, where many features of conversational, spoken language may be lost. Skins, a British teenage series, containing fast-paced dialogues and slang, as well as an abundance of expletives, will be used as an illustration of this topic. The subtitling of only one expletive will be compared across all seven seasons of this television series, by analysing the opening episode of each season, against different circumstances in which particular seasons were subtitled. The study of the corpus of Croatian subtitles of this TV series, based on the analysis of the opening episode of each season of this TV series has been conducted. The article aims to show that the way subtitles are depends on how they were created, under what set of circumstances.